Off-season circulation and characterization of enterovirus D68 with respiratory and neurological presentation using whole-genome sequencing - Cassidy, Hayley; Lizarazo-Forero, Erley; Schuele, Leonard; Van Leer-Buter, Coretta; Niesters, Hubert G. M. (Frontiers in Microbiology, 2023)
To explore an off-season enterovirus D68 (EV-D68) upsurge in the winter season of 2019/2020, we adapted a whole-genome sequencing approach for Oxford Nanopore Technologies for twenty hospitalized patients with accompanying respiratory or neurological presentation. Applying phylodynamic and evolutionary analysis on Nextstrain and Datamonkey respectively, we report a highly diverse virus with an evolutionary rate of 3.05x10-3 substitutions per year (entire EV-D68 genome) and a positive episodic/diversifying selection with persistent yet undetected circulation likely driving evolution. While the predominant B3 subclade was identified in nineteen patients, one A2 subclade was identified in an infant presenting with meningitis. Exploring single nucleotide variations using CLC Genomics Server showed high levels of non-synonymous mutations, particularly in the surface proteins, possibly highlighting growing problems with routine Sanger sequencing for typing enteroviruses. Surveillance and molecular approaches to enhance current knowledge of infectious pathogens capable of pandemic potential are paramount to early warning in health care facilities.